Efficacy of Two Streptokinase Formulations in Acute Myocardial Infarction: A Double-Blind Randomized Clinical Trial - Mojtaba Salarifar (Journal of Tehran University Heart Center, 2009)
Background: We sought to evaluate the efficacy and safety of the different trade forms of streptokinase available in our country, namely Heberkinasa (Heberbiotec, Havana, Cuba) and Streptase (Aventis Behring GmbH, Marburg, Germany).